A genetic enrichment strategy for delay of onset of Alzheimer's disease clinical trials: Biomarkers (non‐neuroimaging)/Use in clinical trial design and evaluation. (7th December 2020) - Lutz, Michael W.; Burns, Daniel K.; Alexander, Robert; Culp, Meredith; Yarnall, David; Haneline, Stephen; Chiang, Carl; Lai, Eric; Metz, Craig; Sundseth, Scott; Guennel, Tobi; Marshall, Scott; et al.
Abstract: Background: A challenge with AD prevention is the timely identification of subjects at risk of cognitive symptom onset, mitigating prohibitive costs associated with the trial size and duration. A biomarker risk assignment algorithm (BRAA) consisting of genotypes at the apolipoprotein E ( APOE ) and translocase of outer mitochondrial membrane 40 homolog ( TOMM40 ) rs10524523 loci ('523) and current age was developed to enrich the TOMMORROW delay of AD onset clinical study. '523 is a poly‐T homopolymer of 14 to 50 residues. For the BRAA, the alleles were categorized by T length as "short" (S: <21), "long" (L: 21‐29), or "very long" (VL: >29). Method: The TOMMORROW study (NCT 01931566) provided a large dataset to assess APOE ‐'523 haplotypes to improve the performance of the BRAA. The original BRAA used phased genetic information to determine risk categories (developed in 150 individuals, verified in 1018 individuals). Because phased haplotype data were not available from the samples genotyped in the TOMMORROW study, an optimized calibration was performed using APOE 3/3 and 4/4 homozygous individuals (n=1625). By maximizing the genetic congruency between the APOE and '523 genotypes, the calibration of the '523 categorical boundaries was optimized. Result: From these haplotype data, the '523 categorical assignments were optimized to S: <19; L: 19‐31; and VL: >31. When these optimized categorical assignments were applied retrospectively to the TOMMORROW study cohort (n=1803), the hazard ratio for the time‐to‐event comparison between the high and low risk placebo groups improved from 3.3 (95% confidence interval [CI] 1.2‐9.0, P =0.023) to 4.3 (95%CI 1.3‐13.7, P =0.015). Applying the refined BRAA to a future delay of AD onset clinical trial would reduce enrollment by 26% for a 5‐year interventional study versus an all‐comers enrollment strategy. Furthermore, a streamlined, kit‐based genotyping assay for APOE and TOMM40 '523 was evaluated and found to yield congruent results with the sequencing‐based method used for genotyping in the TOMMORROW clinical trial. Conclusion: Using phase 3 clinical trial data, the TOMMORROW BRAA demonstrated the ability to enrich delay of onset/prevention of AD studies for subjects more likely to develop cognitive symptom onset during an acceptable timeframe with significant clinical trial cost savings.